Assessment of the Potential of Biomass Gasification for Electricity Generation in Bangladesh - Das, Barun Kumar; Hoque, S. M. Najmul (Journal of Renewable Energy, 2014)
Bangladesh is an agriculture based country where more than 65 percent of the people live in rural areas and over 70% of total primary energy consumption is covered by biomass, mainly agricultural waste and wood. Only about 6% of the entire population has access to natural gas, primarily in urban areas. Electricity production in Bangladesh largely depends on fossil fuel whose reserve is now under threat and the government is now focusing on the alternating sources to harness electricity to meet the continuous increasing demand. To reduce the dependency on fossil fuels, biomass to electricity could play a vital role in this regard. This paper explores the biomass based power generation potential of Bangladesh through gasification technology—an efficient thermochemical process for distributed power generation. It has been estimated that the total power generation from the agricultural residue is about 1178 MWe. Among them, the generation potential from rice husk, and bagasses is 1010 MWe, and 50 MWe, respectively. On the other hand, wheat straw, jute stalks, maize residues, lentil straw, and coconut shell are also the promising biomass resources for power generation which counted around 118 MWe. The forest residue and municipal solid waste could also contribute to the total power generation 250 MWe and 100 MWe, respectively.